Molecular Docking Of Andrographolide To Rennin, HIV-Protease And Tyrosine Enzymes. - Kamaluddin, Achsanuddin; Wahab, Habibah A.; Ismail, Norhayati (2003)
AutoDock 3.0 was used to dock andrographolide,a diterpenoid from the herb Andrographis Paniculata Nees, to the active site of Renin, HIV -1 Protease, and Tyrosine kinase enzymes. The andrographotide structure was prepared using Insight's ll Bui[der module.